Effect of Blend of Metanil Yellow and Tartrazine on Different Organs of Albino Rat - Abd Elaziz, Mai Ahmed; Elgallad, Ghada Mostafa; ELhanboly, Hala Mohammed; Raouf Saleh, Amal; Maklof, Mohammed (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Tartrazine and metanil yellow are organic azo dyes widely used in food products, drugs, and cosmetics. The present study was conducted to evaluate the toxic effect of these food colors on the liver, and kidneys of albino rats. The study also evaluates the protective effect of quercetin as an antioxidant against the toxic effect of these food colors. Methods: Eighty adult albino rats were divided into 8 groups. Control group, 3 groups were treated with a blend of tartrazine and metanil yellow in 3 doses of 25, 50, and 75 mg/kg for 30 days by gavage, one positive control group was treated with quercetin 50 mg/kg for 30 days, and three groups were treated with the blend of tartrazine and metanil yellow plus 50 mg/kg of quercetin. At the end of the experiment, serum samples were collected to evaluate liver and kidney functions. Liver, kidney samples were fixed in 10% formalin and routinely prepared for paraffin sectioning and staining for histopathological examination. Results: The study showed a significant elevation of liver and kidney function after treatment with the food color blend. Also, a significant improvement in liver and kidney function was observed after treatment with quercetin. Histopathological examination showed mild to moderate changes in the liver and kidney which improved after quercetin treatment. Conclusion: The current sub-chronic study concluded that a blend of tartrazine and metanil yellow caused significant biochemical and histological changes in different organs of albino rats. Therefore, prolonged consumption of these substances leads to adverse effects on human health. Also, quercetin is vital in protecting the body against the toxic effects of food color blends.